2015
DOI: 10.1128/aem.01012-15
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Accumulation of Glycine in Polyphosphate-Accumulating Organisms in Activated Sludge, a Novel Storage Mechanism under Dynamic Anaerobic-Aerobic Conditions

Abstract: Dynamic anaerobic-aerobic feast-famine conditions are applied to wastewater treatment plants to select polyphosphate-accumulating organisms to carry out enhanced biological phosphorus removal. Acetate is a well-known substrate to stimulate this process, and here we show that different amino acids also are suitable substrates, with glycine as the most promising.13 C-labeled glycine and nuclear magnetic resonance (NMR) were applied to investigate uptake and potential storage products when activated sludge was fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 48 publications
(77 reference statements)
2
35
0
Order By: Relevance
“…The strength of the current FISH-Raman method is that it does not rely on such inferences and that it can directly measure the polymer in question in its native state at a single-cell level. It has been shown that T. elongata can grow by fermentation 19 , and probe-defined Tetrasphaera in full-scale EBPR plants likely ferment glucose after several of days anaerobic conditions 54 , so fermentation is likely a key metabolic feature in tandem with poly-P formation/degradation in their successful competition to many other microbes in EBPR plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the current FISH-Raman method is that it does not rely on such inferences and that it can directly measure the polymer in question in its native state at a single-cell level. It has been shown that T. elongata can grow by fermentation 19 , and probe-defined Tetrasphaera in full-scale EBPR plants likely ferment glucose after several of days anaerobic conditions 54 , so fermentation is likely a key metabolic feature in tandem with poly-P formation/degradation in their successful competition to many other microbes in EBPR plants.…”
Section: Resultsmentioning
confidence: 99%
“…Annotation of representative genomes for the genus suggests that glucose could be stored as glycogen (but not PHAs) under anaerobic conditions, and some un-polymerised fermentation products and amino acids have been shown to accumulate in the cell. Under subsequent aerobic conditions, glycogen and accumulated intracellular substrates are suggested to be utilized for growth and the replenishment of poly-P reserves 18; 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Three Tetrasphaera-related clades, including Clade 1, Clade 2A, and Clade 3 were dominant in the culture at similar relative abundances. Although Tetrasphaera Clade 1 and a portion of Clade 3 cannot take up acetate, they are all capable of fermentation, which leads to Tetrasphaera thriving in WRRFs that receive complex organic matter (Nguyen et al, 2011(Nguyen et al, , 2015. In the side-stream reactor of an S2EBPR system, it is likely that Tetrasphaera may play a crucial role that firstly fermenting complex carbon sources for energy generation, and Accumulibacter could then take up the fermentation products (e.g., acetate or propionate) generated by Tetrasphaera for PHA storage.…”
Section: Microbial Dynamicsmentioning
confidence: 99%
“…The acquired data indicated that this is not the case for T. elongata and that it does indeed show a high level of metabolic robustness and readiness [39]. The theoretical advantage of being able to keep growing without major metabolic adaptations will be enhanced under in situ conditions as T. elongata can store excessive amounts of poly-P for rapid supplementation of energy or accumulation of carbon substrates under anaerobic conditions [16]. The proteomic and metabolomic data helps to complement the existing metabolic model [15] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lp2 and E. coli str. K-12 were cultivated in modified R2A (minimal) medium [16] to be comparable with previous studies. Inoculation was performed from liquid overnight cultures to an optical density (OD) at 600 nm of 0.01.…”
Section: Methodsmentioning
confidence: 92%